Characteristics of handwriting quality and speed in adults with autism spectrum disorders. (February 2018) - Godde, Anaïs; Tsao, Raphaele; Gepner, Bruno; Tardif, Carole
Highlights: Adults with ASD had handwriting difficulties on quality and speed production. Macrographia was not identified as a characteristic of handwriting quality. Developmental age predicts handwriting quality in adults with ASD. Abstract: Background: Handwriting difficulties affecting production quality and speed have been identified in children and adolescents with autism spectrum disorders (ASD), and several perceptual‐motor impairments have been shown to contribute to these difficulties. There has been only one study of handwriting in adults with ASD, and this focused on letter size, reporting macrographia. The present study was therefore intended to explore the other features of handwriting and the role of perceptual‐motor skills in this activity in adults with ASD. Method: We recruited a group of adults with ASD ( n  = 21) and two typically developing control groups, matched on either chronological ( n  = 21) or developmental ( n  = 21) age. Participants performed a handwriting copy task to assess handwriting speed and quality, and five perceptual‐motor tasks (finger dexterity, fine motor coordination, graphomotor activity, visuomotor integration, and visual attention). Results: Adults with ASD had significantly poorer handwriting quality than adults in the two control groups, and lower handwriting speed than adults of the same chronological age. Developmental age was the best predictor of handwriting quality in adults with ASD, whereas visuomotor integration was the best predictor in the control group matched on developmental age. None of the factors we tested influenced production speed in adults with ASD. Conclusions: Handwriting in adults with ASD appears to show weaknesses and peculiarities. Further studies are needed to explore alternative predictive factors for handwriting speed and quality in adults with ASD, in order to improve handwriting and consequently increase employment opportunities for this population.